PENINGKATAN KETERAMPILAN MENULIS PUISI MELALUI MODEL PROJECT BASED LEARNING BERBASIS GALERI PUISI PADA PESERTA DIDIK KELAS VIII SMP NEGERI 7 TANJUNGPINANG - Dinda Jannaty, Bhaity; Reza Putri Aisyah, Raja; Nurul Suhendra, Rizky; Ariance Loren, Fabio Testy; Novita, Mira (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of the Project based learning (PjBL) model based on a poetry gallery and prove an increase in poetry writing skills among class VIII.4 students at SMP Negeri 7 Tanjungpinang. The study was motivated by students' low poetry writing skills, evidenced by initial data showing only 40.00% achieved the minimum passing grade of 70. This classroom action research (PTK), based on the Kemmis and McTaggart model, was carried out in two cycles involving 45 students, each cycle comprising planning, implementation, observation, and reflection. Data were collected through tests, observation, interviews, and documentation, and analysed both quantitatively and qualitatively. Results showed consistent, significant improvement across cycles. The mean score rose from 65.13 in the pre-cycle to 72.91 in Cycle 1 and 80.29 in Cycle 2. Classical learning achievement increased from 40.00% to 75.56% in Cycle 1 and reached 100.00% in Cycle 2, exceeding the 75% success indicator. The average N-Gain Score of 0.42 indicates moderate effectiveness. The standard deviation also decreased from 15.07 to 7.72, reflecting more equal learning outcomes among students. In conclusion, the PjBL model based on a poetry gallery effectively enhances students' poetry writing skills while narrowing the ability gap among class VIII junior high school students.